CONSIDERATIONS ON THE TARGET SIZE IN A WALL-LESS NANODOSIMETER. Issue 1 (11th December 2018) - Rabus, Hans; Hilgers, Gerhard; Ngcezu, Sonwabile Arthur; Bug, Marion
Abstract: In nanodosimetry, the ionization component of charged particle track structure is characterized by measuring the frequency distribution of ionizations in target volumes that simulate nanometric sites in liquid water. For the Ion Counter nanodosimeter at PTB, the sensitive volume is defined by the electrical field and the extraction aperture. In this paper, a procedure is presented to define a cylindrical effective measurement target based on the second moments of the detection efficiency map. An analytical model of the efficiency map is developed to investigate the dependence of the simulated site size on the nanodosimeter's operating parameters. Within the limits of the simplifying assumptions, the model gives a reasonable approximation of the efficiency map.